Marine microbiology - Paul, John H. (Methods in microbiology, 2001)
Written by experts in the field, Marine Microbiology presents the latest experimental techniques in the detail required for modern environmental microbiological research. Chapters start with the introduction and background of a particular method, followed by a concise description of the procedures involved. There is also a list of vendors who supply critical components which includes names, addresses, and websites at the end of each chapter. Key Features * Covers both established and novel current methods * Historical perspective * Enumeration of autotrophic picoplankton, bacteria and viruses * Fingerprinting Viral Assemblages by Pulsed Field Gel electrophoresis (PFGE) * Fluorescence in situ hybridization with rRNA-targeted oligonucleotide probes * Detection of phytoplankton by remote sensing * Marine pollution microbiology * Microbes in extreme environments * List of suppliers provided at end of each chapter * Colour plate section.